Structural changes in the retina as a potential biomarker in Parkinson's disease: an approach from optical coherence tomography - Poveda, Santiago; Arellano, Ximena; Bernal-Pacheco, Oscar; Valencia López, Alejandro (Frontiers in Neuroimaging, 2024)
Introduction Parkinson's disease (PD) presents challenges in early diagnosis and follow-up due to the lack of characteristic findings. Recent studies suggest retinal changes in PD are possibly indicative of neurodegeneration. We explored these changes using optical coherence tomography (OCT) to assess retinal nerve fiber layer (RNFL) and ganglion cell complex (GCC) thickness. Methods Thirty PD and non-PD patients were matched according to demographic characteristics and OCT and clinical evaluations to rule out other neurodegenerative and visual diseases. Results We observed a significant thinning of the RNFL in patients diagnosed with PD compared to non-PD patients (p = 0.015). Additionally, this reduction in RNFL thickness was found to correlate with the severity of the disease (p = 0.04). Conclusion The OCT serves as a tool for quantifying neurodegeneration in PD, showing a significant correlation with disease severity. These findings suggest that OCT could play a crucial role as a potential biomarker in the diagnosis and monitoring of PD.